Microstructure and texture evolutions in AZ80A magnesium alloy during high-temperature compression - Xingwang Duan; Junjie Liu; Peng Li; Baosheng Liu; Jiachen Liu (Materials Research Express, 2021)
In the process of thermal deformation, the microstructure and texture evolutions of AZ80A magnesium alloy have an important influence on its properties. In order to reveal the evolutions of microstructure and texture of AZ80A magnesium alloy during hot deformation, isothermal compression tests were performed on a Gleeble-3800 thermal simulator at a temperature range of 623 K∼723 K, a strain rates range of 0.001 s ^−1 ∼1 s ^−1 , and a deformation rate of 20%∼60%. Based on the analysis of the true stress-true strain curves under the given deformation conditions, the hyperbolic sinusoidal constitutive model and dynamic recrystallization (DRX) kinetics model were established by regression method, respectively. The DRX behavior, microstructure and texture evolutions during the thermal compression were then analyzed by optical microscopy (OM) and electron backscattered diffraction (EBSD). The results show that an increasing deformation temperature and decreasing strain rate greatly support the development of DRX of AZ80A magnesium alloy. As the deformation rate increases, DRX of AZ80A alloy is gradually and more sufficiently developed, and the dominated deformation mechanism is gradually transformed from the {0001} base slip to { $10\bar{{\rm{1}}}0$ } cylinder slip. Moreover, the low-angle grain boundaries (between 5° and 75° in deformation rate of 20%) gradually transform into large-angle grain boundaries (between 50° and 90° in deformation rate of 60%). Besides, the texture is gradually transformed from a base texture paralleled to compression direction to a texture perpendicular to compression direction, where twinning, rather than slip, is the main deformation mechanism. The results in this study provides a guidance in the hot forming process of AZ80A magnesium alloy.